Free Latissimus Dorsi Flap With Femoral Artery End-to-Side Anastomosis for Perineal Reconstruction Following Fournier's Gangrene. (8th October 2020) - Duncan, Anna; Byun, Stephanie; Paletz, Justin
Fournier's gangrene is a necrotizing infection of the soft tissue structures of the perineum that can extend quickly, requiring aggressive and repeated surgical debridement. This can result in extensive tissue loss and functional impairment, creating reconstructive challenges for plastic surgeons. We present a case of Fournier's gangrene which resulted in complete loss of the pelvic floor musculature and functional loss of the urinary and fecal outlets. Given the extent of the defect and involvement of areas that would traditionally be used as donor site for local and regional flaps, reconstruction was sought with a free latissimus dorsi flap in combination with split-thickness skin grafting following serial debridement and negative pressure wound therapy. The patient survived and made a satisfactory recovery.